Age and sex characteristics of behavioral risk factors and adherence to a healthy lifestyle in Muscovites - S. E. Evstifeeva; A. V. Kapustina; E. L. Nikonov; A. N. Dotsenko; E. V. Prokhorenko; Yu. A. Balanova; A. E. Imaeva; N. S. Karamnova; G. A. Muromtseva; B. M. Nazarov; S. A. Shalnova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To study the sex characteristics of behavioral risk factors for chronic noncommunicable diseases and to assess the integral indicator of adherence to a healthy lifestyle in Muscovites within the AEGIDA-Moscow study.Material and methods. A random sample from the adult population of Moscow aged ≥ 18 years (n=4063; men, 40,9%) was used. The response rate was 78,1%. The standard survey was conducted using an international questionnaire based on the WHO STEPS Instrument. The following parameters were analyzed: smoking, alcohol consumption, physical activity (PA), consumption of vegetables/fruits and salt. High integral indicator of adherence to a healthy lifestyle was recorded in case of normal PA, sufficient intake of vegetables/fruits, non-smoking, and without excessive intake of salt and alcohol.Results. The smoking prevalence in Moscow was 18,3%. Among men, this indicator was more than 2 times higher than among women (28,0 and 11,4%, respectively, p<0,05). On average, the prevalence of low PA among men and women did not differ significantly (27,8 and 29,3%, p>0,5). The prevalence of insufficient consumption of vegetables/fruits (<400g) (men, 66,8%, women, 58,3%), excessive (>5 g) consumption of salt (60,3 and 41,9%, respectively) and alcohol (6,7 and 4,4%, respectively), and an unfavorable integral indicator of adherence to a healthy lifestyle (47,1 and 30,7%, respectively) among men was higher than among women.Conclusion. The prevalence of smoking, excessive consumption of alcohol and salt, and insufficient intake of fruits/vegetables among men was significantly higher than among women. The prevalence of low PA in the male and female cohorts did not differ significantly. Almost half (47,1%) of men and a third (30,7%) of women have an unfavorable integral indicator of adherence to a healthy lifestyle.